Rainforest colors - Canizares, Susan (New York : Scholastic, 1998)
Photographs and simple text explore the unusual colors of birds, plants, and frogs in the Amazon rainforest.
"Scholastic early childhood"--Includes index
Keywords: Color -- Juvenile literature; Rain forest ecology -- Juvenile literature